2002
DOI: 10.1046/j.1365-2400.2002.00282.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of stocking size on the first winter survival of whitefish, Coregonus lavaretus (L.), in the Gulf of Bothnia, Baltic Sea

Abstract: The anadromous whitefish, Coregonus lavaretus (L.), is the most numerous fish species stocked in the Gulf of Bothnia, Baltic Sea. One‐summer‐old‐whitefish fingerlings are mostly 8–10 cm long when released annually in September–October, whereas the wild whitefish are 10–12 cm at that time. About 6 million, one‐summer‐old, spray‐marked, whitefish were released in the northern and central parts of the Gulf in 1995–1998. To study the effect of the stocking length on the survival of the marked fish, the length of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
(11 reference statements)
0
4
0
Order By: Relevance
“…Salojärvi (1991) found that stocking larger fingerlings of European whitefish did not necessarily increase survival rates. The mean size of the fish from five stocking events in this European study ranged from 76 to 115 mm and from 3.0 to 9.3 g. In contrast, Jokikokko et al (2002) suggested that larger fall fingerlings of the same European whitefish species stocked in the Baltic Sea had greater survival rates than smaller ones. The mean size of cohorts stocked in that study ranged from 88 to 106 mm, which is within the range of sizes stocked in the Salojärvi experiment but smaller than the fingerlings stocked into Lake Simcoe.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Salojärvi (1991) found that stocking larger fingerlings of European whitefish did not necessarily increase survival rates. The mean size of the fish from five stocking events in this European study ranged from 76 to 115 mm and from 3.0 to 9.3 g. In contrast, Jokikokko et al (2002) suggested that larger fall fingerlings of the same European whitefish species stocked in the Baltic Sea had greater survival rates than smaller ones. The mean size of cohorts stocked in that study ranged from 88 to 106 mm, which is within the range of sizes stocked in the Salojärvi experiment but smaller than the fingerlings stocked into Lake Simcoe.…”
Section: Discussionmentioning
confidence: 57%
“…The size difference between fingerling fish at age 1, after their first winter in the lake, and yearling fish remains unknown. However, we expect that growth of fingerling fish would have slowed considerably during their first winter in the lake (Jokikokko et al 2002), resulting in a smaller size than the yearling fish maintained in the hatchery. Any difference in size that may have existed between fish of these two stocking strategies was undetectable by age 6.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whitefish stocks have undergone large‐scale changes since the 1950s (Urho, ). Due to the decline in natural stocks and intense hatchery releases of young fish (Jokikokko & Huhmarniemi, ; Jokikokko, Leskelä, & Huhmarniemi, ), the stock composition of the whitefish sea catch has changed over time. Nowadays, most of the captured whitefish are anadromous: 60%–70% of the catch in the northern GoB and nearly 100% in the southern GoB consists of anadromous whitefish (Raitaniemi & Manninen, ).…”
Section: Introductionmentioning
confidence: 99%